PENINGKATAN PRESTASI HASIL BELAJAR DAN KETERAMPILAN MAHASISWA MELALUI PROJECT BASED LEARNING PADA MATA KULIAH RIAS WAJAH FANTASI JURUSAN PKK TATA RIAS FT UNM - Burhanuddin, Izmi (Universitas Negeri Makassar, 2025)
This study aims to determine the improvement in academic achievement and skills of Makeup students through the implementation of the Project-Based Learning (PjBL) model in the Fantasy Makeup course at the Department of Family Welfare Education (PKK), Faculty of Engineering, Universitas Negeri Makassar. Academic achievement and student engagement are essential aspects to enhance in the learning process, requiring an innovative instructional model. One effective approach to improving student achievement and skills is project-based learning (PjBL). This learning model is designed to provide a more active, creative, and innovative learning experience by directly engaging students in fantasy makeup projects. The research method used is classroom action research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects are sixth-semester Makeup students in the Department of Family Welfare Education (PKK), Faculty of Engineering, Universitas Negeri Makassar. The results of the study indicate that the implementation of Project-Based Learning (PjBL) can enhance students' academic achievement and skills in designing, conceptualizing, and applying fantasy makeup techniques. Moreover, this method also increases students' self-confidence in developing their creativity.